Selected texts of legal instruments in international environmental law. (United Nations Environment Programme, 2005)
Each of our actions, each of our decisions, has a direct link to whether the world as we know it today will survive, or succumb during the lifetime of our children. Success in combating environmental degradation is dependent on the full participation of all actors in society. One of the major challenges that legal stakeholders in developing countries and countries with economies in transition face is getting access to relevant information and material on environmental law. This publication is designed to meet that demand and serve as a source of reference of basic documents on international environmental law.--Publisher's description.